The The Effect of 6-Week Interval and Continuous Training with Zizphus Vulgaris Extract Supplementation on Hippocampus’s BDNF Male Wistar Rats - Bagherinia 1, Azam; Banparvari 2*, Maryam; Mogharnasi 3, Mehdi; Sarir 4, Hadi; Naderi 5, Aynollah (Shahroud Journal of Medical Sciences, 2020)
Background: The aim of the study was to compare the effect of 6-week interval and Continuous training with Zizphus Vulgaris Extract supplementation on the hippocampus’s BDNF male Wistar rats. Methods: Among 36 male rats (250-350 gr), randomly after adjusting the body weight, 6 rats were separated as the control group. 30 rats were divided into 5 groups: Continuous group (n=6), Interval group (n=6), Continuous with Zizphus Vulgaris Extract group (n=6), Interval with Zizphus Vulgaris Extract group (n=6) and Zizphus Vulgaris Extract group (n=6). The training groups completed 8 weeks of the training program, 5 days/week according to protocol. The Endurance Continuous protocol includes running exercise on a treadmill for, 10 m/min, 10 min/day to up 16 m/min, 40 min/ day. Endurance Interval protocol includes running exercise on a treadmill for, 5*4 min, with intensity 10 m/min to up 23 m/min, 52 min/ day. The Zizphus Vulgaris Extract group, every 6 weeks, each rat consumed 400 mg/kg.day and 1.5 mL. At the end of the intervention, the animals were euthanized and the hippocampus’s BDNF was measured. Data were analyzed using one way ANOVA tests (Pvalue<0.05). Results: Interval with the Zizphus Vulgaris Extract group had significantly increased hippocampus’s BDNF compared to control and Zizphus Vulgaris Extract groups ( respectively p= 0.01, p= 0.02). Other comparisons were not significant. Conclusions: Interval with Zizphus Vulgaris Extract induce more effective favorable changes in the hippocampus’s BDNF in male rats. Likely, that be the best Strategy to prevent negative effects on the hippocampus’s BDNF decrease. Keywords: Interval training, Continuous training, Zizphus Vulgaris extract supplementation, Hippocampus’s BDNF, male wistar rats.